Estudio geológico estructural y elaboración del plan de seguridad minera, en el área minera "Bravo" (Código 2250.1) de la parroquia Bella María, cantón Santa Rosa, provincia de El Oro. - Tamayo Quiñónez, Edison Patricio (2013)
MINING AREA "BRAVO” is located in the Valle Hermoso sector, Bella María Parish, Canton Santa Rosa. El Oro Province covers an area of 200 hectares contiguous mining, of which 15 hectares make up the operating area. With the topographic survey conducted special modeling yielded a mining project, which allowed obtaining the actual terrain topography both surface-mines in an area of 32.56 hectares which make operating activities BRAVO MINING AREA. Based on geological information was achieved to map Geological Surface and Structural for BRAVO MINING AREA, which is located on a cuarzo - diorítico intrusive presence of gaps, light gray andesite, also was determined faults with direction from 110 ° to 140 ° with variable dips ranging from 65 ° to 75 ° NE. From the geological point it was concluded that the area of the concession area is constituted by a complex intrusive basically calc alkaline type granodiorite with coarse texture, varying mainly equigranular locally finer grained faces. Likewise we find a series of mineralized fault breccia’s present in the walls of the gallery of the mine workings, which are colored gray in the presence of pyrite, chalcopyrite and galena possible, with a direction of N70 ° E and dip between 65 ° to 75 ° SE. The geological survey conducted mineralized allowed locating various sites in the presence of pyrite, chalcopyrite, biotite and galena, disseminated in the body of the gaps and sometimes within quartz veinlets and segregations. The analysis of different variables to identify and evaluate the occupational risks in the development of activities allowed knowing the main weaknesses within both surface mine so it raises some alternatives to correct these shortcomings and improve the Labor Safety the BRAVO MINING AREA. The development of the Mine Safety Plan MINING AREA BRAVO is aimed at improving signaling both surface-mine, also with proper storage, transportation and handling of explosives, fuel and oil waste, tailings, mine water, and also the control of gases, dust and noise.